The Difference of Sodium Intake, Physical Activities and Psychological Problems of Patients Suffering from Hypertension in Rural and Urban Areas - Heny Suseani Pangastuti; Melyza Perdana; Dewi Agustina Wati; Hatifah Ihsanda Tien Melati; Rizki Latifah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2018)
Introduction: The patients suffering from hypertension require treatment to prevent the complications by performing both pharmacological and non-pharmacological hypertension management. This research aims at revealing the difference of sodium intake, physical activities, and psychological problems in patients suffering from hypertension in rural and urban areas. Methods: This descriptive-quantitative research employs a cross sectional design. The research was conducted at Gondokusuman Community Health Center 1 as the representation from the urban areas and Cangkringan Community Health Center as the representation from the rural areas. There were 81 patients from rural areas and 74 from urban areas. Data were collected using a consecutive sampling technique with Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), Global Physical Activity Questionnaire (GPAQ) and Depression, Anxiety, Stress Scale 42 (DASS 42). The data analysis was conducted using both chi-square test and independent t-test. Results: The result of independent t-test for sodium intake was at p = 0.669 (p > 0.005). The result of analysis using chi-square test for physical activity was at p = 0.000 (p < 0.05). The result of analysis using chi-square test for depression level is at p = 0.964 (p > 0.05), anxiety level at p = 0.005 (p < 0.05) and stress level at p = 0.846 (p > 0.05). Conclusions: There are some differences in physical activities and anxiety levels in patients suffering from hypertension in rural and urban areas.